Retrograde Surgical Placement of a Thoracic Epidural Catheter in a Patient Undergoing Combined Thoracic and Spinal Surgery - Davis VB; Li M; Li FM; Komatsu R; Wu J (International Medical Case Reports Journal)
Vanessa B Davis,1 Mark Li,1 Flora Mian Li,1 Ryu Komatsu,2 Jiang Wu1 1Department of Anesthesiology and Pain Medicine, University of Washington Medical Center, Seattle, WA, USA; 2Multi-Specialty Anesthesiology, Integrated Hospital-Care Institute, Cleveland Clinic, Cleveland, OH, USACorrespondence: Jiang Wu, Email jiangwu@uw.eduAbstract: Epidural anesthetic techniques for postoperative analgesia are rarely considered in spinal surgery, and high thoracic epidural analgesia (TEA) is considered medically risky. We present a successful case of surgical retrograde placement of a thoracic (T6-T7) epidural catheter under direct surgical visualization via T2 laminectomy in a patient who underwent combined thoracotomy and spinal surgery. TEA was confirmed by epidurogram, provided adequate postoperative pain relief, and the patient was discharged home three days post-surgery.Keywords: thoracic epidural analgesia, retrograde, laminectomy, thoracotomy